Manifestations of intellectual disability, dystonia, and Parkinson's disease in an adult patient with ARX gene mutation c.558_560dup p.(Pro187dup) - Mittal Balraj; Arvio Maria; Lähdetie Jaana; Koivu Hannu; Sohlberg Antti; Pekkonen Eero (Hindawi, 2025)
We describe a 38-year-old male patient with intellectual disability and progressive motor symptoms who lacked an etiological diagnosis for many years. Finally, clinical exome sequencing showed a likely pathogenic variant of the ARX gene suggesting Partington syndrome. His main symptoms were mild intellectual disability, severe kinetic apraxia, resting and action tremor, dysarthria, tonic pupils, constant dystonia of one upper limb, and focal dystonia in different parts of the body, axial rigidity, spasticity, epilepsy, and poor sleep. Another likely pathogenic gene variant was observed in the PKP2 gene and is in accordance with the observed early cardiomyopathy. Single-photon emission computed tomography imaging of dopamine transporters showed a reduced signal in the basal ganglia consistent with Parkinson’s disease. Therapies with a variable number of drugs, including antiparkinsonian medications, have yielded poor responses. Our case report extends the picture of the adult phenotype of Partington syndrome.